2017
DOI: 10.1002/nbm.3869
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted imaging features of breast tumours and the surrounding stroma reflect intrinsic heterogeneous characteristics of molecular subtypes in breast cancer

Abstract: Breast cancer heterogeneity is the main obstacle preventing the identification of patients with breast cancer with poor prognoses and treatment responses; however, such heterogeneity has not been well characterized. The purpose of this retrospective study was to reveal heterogeneous patterns in the apparent diffusion coefficient (ADC) signals in tumours and the surrounding stroma to predict molecular subtypes of breast cancer. A dataset of 126 patients with breast cancer, who underwent preoperative diffusion-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
(93 reference statements)
4
17
0
Order By: Relevance
“…This phenomenon may be attributed to the high cellular density and the restriction of water molecules in malignant tumors (30). A recent study further revealed that the features of DWI could reflect the intrinsic heterogeneous characteristics of molecular subtypes in BC (31). Our study further quantified the ADC derived from RS-EPI DWI and demonstrated that the ADC value was statistically significant in identifying HER-2-enriched BC and TNBC with an AUC of 0.763 (95% CI: 0.681-0.904).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be attributed to the high cellular density and the restriction of water molecules in malignant tumors (30). A recent study further revealed that the features of DWI could reflect the intrinsic heterogeneous characteristics of molecular subtypes in BC (31). Our study further quantified the ADC derived from RS-EPI DWI and demonstrated that the ADC value was statistically significant in identifying HER-2-enriched BC and TNBC with an AUC of 0.763 (95% CI: 0.681-0.904).…”
Section: Discussionmentioning
confidence: 99%
“…40 Lower ADC values in estrogen receptor (ER) or progesterone receptor (PgR) positive tumors have already been reported in many papers. [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Kawashima et al 53 demonstrated significantly lower D and ADC values in luminal B compared with luminal A tumors. Iima et al 58 reported significantly lower sADC 200-1500 values in PgR expression.…”
Section: Breastmentioning
confidence: 99%
“…However, to predict tumor characteristics, only a single parametric MRI is usually used. For example, studies indicate that radiomic analysis of MRI may be helpful in predicting breast cancer subtypes [13][14][15][16], neoadjuvant chemotherapy responses [17][18][19], Ki-67 expression level [20][21][22], pathological stage [23], histological grade [24], tumor malignancy [25,26], and breast cancer risk [27] based on either DCE-MRI or DWI. These studies were performed without considering complementary information that could be provided by different parametric images.…”
Section: Introductionmentioning
confidence: 99%